LEADing together: Partnerships for a Healthier DeKalb - April Hermstad; MJ Gathings; Jen Isher-Witt; Felicia Arriaga; Corre Robinson (Georgia Southern University, 2017)
Background: In 2014, the DeKalb County Board of Health (DCBOH) received a three-year Racial and Ethnic Approaches to Community Health (REACH) grant to work with community partners to address health disparities among African Americans in DeKalb County. The project, called Local Efforts toward Addressing Disparities in DeKalb (LEAD DeKalb), relies on a network of partnerships to implement community-based interventions that promote healthy eating and physical activity among African Americans throughout low-income parts of DeKalb County. Methods: The evaluation team developed an online survey to assess LEAD DeKalb staff and partner satisfaction with the partnerships created and the work completed through LEAD DeKalb thus far (n=20, response rate of 71.4%). The 20-question survey was adapted primarily from two sources: the Wilder Collaboration Factors Inventory and the Program Sustainability Assessment Tool. Data analysis was limited to basic descriptive information such as frequencies, percentages, and averages, with comparisons made between DCBOH staff and partners. Results: Partners reported that their organization benefits from being involved in the partnership and attributed a variety of factors to the success of the partnership, including: bringing together diverse stakeholders; exchanging information/knowledge; sharing resources; and developing a shared mission and goals. Identifying new partners and developing a sustainability plan that includes funding, community support, and strong partnerships were identified as areas for improvement. Relevant qualitative findings from key informant interviews were also presented. Conclusions: Two main themes emerged from the data: (1) the network of partnerships is valuable and strong, but may benefit from new partners, and (2) resources (especially funding) are critical for implementing and sustaining the work of the partnership. Taken together, these findings suggest that partnerships are best conceptualized as ongoing processes rather than tasks to complete; and expanding social networks and learning communities allows partners to leverage social, human, and financial capital well beyond the grant period. Key words: partnerships, stakeholders, engagement, community-based interventions, evaluation, sustainability